2014
DOI: 10.1021/la404251h
|View full text |Cite
|
Sign up to set email alerts
|

A Vapor-Phase Deposited Polymer Film to Improve the Adhesion of Electroless-Deposited Copper Layer onto Various Kinds of Substrates

Abstract: The adhesion of electrodeposited metal film to polymeric circuit board substrate is one of the key elements to successful miniaturization of electronic devices. However, as the size of the circuit pattern continuously decreases, a novel method is urgently required to increase the adhesion of the metal film on the substrate, especially on the smooth surface, which is critical to decrease the minimum feature size of the metal pattern. In this research, we developed an adhesion promoter layer by depositing metal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Poly (4‐vinylpyridine) (P4VP) has been used in the past to modify substrates, allowing them to uptake silver ions. It achieves this through its strong ability to chelate with transitional metal ions . P4VP polymers can be directly coated onto substrate by physical absorption, however, these coating will eventually come off during the long‐time emersion in acrylic solution for chemical engraving.…”
Section: Resultsmentioning
confidence: 99%
“…Poly (4‐vinylpyridine) (P4VP) has been used in the past to modify substrates, allowing them to uptake silver ions. It achieves this through its strong ability to chelate with transitional metal ions . P4VP polymers can be directly coated onto substrate by physical absorption, however, these coating will eventually come off during the long‐time emersion in acrylic solution for chemical engraving.…”
Section: Resultsmentioning
confidence: 99%
“…You et al reported on a p4VP‐based adhesion promoter layer that uses the iCVD process. The adhesion promoter layer was found to be capable of metal chelation in inducing the adhesion of the metal layer to various organic and inorganic substrates . The adhesion promoter particularly enhanced adhesion between the electroless plated Cu layer and the printed circuit board (PCB) substrate over a short process period and with conformal coverage (Figure a).…”
Section: Icvd For Surface Treatmentsmentioning
confidence: 99%
“…a) Overall scheme and SEM image of the bonding between electroless deposited Cu layer and substrate using an adhesion promoter layer, p4VP . b) Digital image the PCB‐coated cloth and operational 7‐segment display using the PCB‐coated cloth before and after the washing cycle .…”
Section: Icvd For Surface Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The strong interand intra-molecular interactions in the molecular chains for standard PI films make it nearly impossible to be processed by hot-adhesion bonding procedures. In practical applications, such as in fabrication of flexible copper clad laminates (FCCLs) for advanced microelectronic assembly [6][7][8][9][10], PI film substrates have to be adhered to metals or other matrixes by the aid of additional epoxy, acrylic, silicone, or fluoro-polymer adhesives [11][12][13]. This would inevitably cause undesirable thickness increase for the components or severe reliability issues in extreme conditions.…”
Section: Introductionmentioning
confidence: 99%